Implikasi Praktis Konsep Teologis Munus Triplex bagi Pendidik Kristen [Practical Implications of the Munus Triplex Theological Concept for Christian Educators] - Arthur Chandra (Universitas Pelita Harapan, 2024)
This paper discusses the practical implications of the theological concept of the three roles of Christ's office which is one of the distinctive identities of Reformed theology with the term munus triplex in the realm of Christian education. This theological concept explains the identity and work of Christ in salvation by carrying out the role of office as prophet, priest and king. The purpose of this study is to explain and apply the concept of Munus Triplex as one of the tools to manifest Christian theology concretely and specifically in the pedagogical context by presenting the identity and work of Christ as the centre of salvation, where Christian educators need to build it through certain habits with students continuously. The habit is built intentionally in presenting educators as the image of Christ through the implementation of the role of the office of prophet, priest and king. Thus, the educator is expected to see Christ through the habits built by the Christian educator so that the educator can grow to love God and resemble Christ more and more. BAHASA INDONESIA ABSTRACT: Tulisan ini membahas tentang implikasi praktis dari konsep teologis tiga peran jabatan Kristus yang menjadi salah satu identitas khas dari teologi Reformed dengan istilah munus triplex dalam ranah pendidikan Kristen. Konsep teologis ini menjelaskan mengenai identitas dan karya Kristus dalam keselamatan dengan mengemban peran jabatan sebagai nabi, imam dan raja. Tujuan dalam penelitian ini adalah menjelaskan dan mengaplikasikan konsep Munus Triplex sebagai salah satu tools untuk mengejawantahkan teologi Kristen secara konkrit dan partikular dalam konteks pedagogik dengan menampilkan identitas dan karya Kristus sebagai pusat keselamatan, dimana pendidik Kristen perlu membangunnya melalui kebiasaan tertentu dengan naradidik secara kontinyu. Kebiasaan tersebut dibangun secara intensional dalam menampilkan pendidik sebagai gambar Kristus melalui pelaksanaan peran jabatan nabi, imam dan raja. Dengan demikian naradidik diharapkan dapat melihat Kristus melalui kebiasaan yang dibangun pendidik Kristem sehingga naradidik dapat bertumbuh semakin mencintai Tuhan dan menyerupai Kristus.